Influence of Different Factors on Productivity of Reed Growths (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The study shows results of research on reed productivity and on factors influencing this productivity. The research was performed during winter period from 2010 until 2012 in 23 natural and artificial water bodies of Latvia. The author of this study analyzed indexes of reed growth productivity and found regularities that statistically significantly (p less then 0,05) explain changes of reed productivity in water bodies depending on individual reed growing conditions in each water body. It is established that the productivity of reed growth depends on the amount of nutrients in the water of water body and that this productivity rises if the total concentration of nitrogen and phosphorus in the water is increased. The reed productivity is lower in clearer water. This parameter may be used in order to evaluate the amount of extractable biomass. The coherence is characterized by statistically significant (p less then 0,05) regression equation.